2018
DOI: 10.1136/bmjopen-2017-019097
|View full text |Cite
|
Sign up to set email alerts
|

Fatty liver index, albuminuria and the association with chronic kidney disease: a population-based study in China

Abstract: ObjectivesThe effects of lipid metabolism disorder on renal damage have drawn much attention. Using the fatty liver index (FLI) as a validated indicator of hepatic steatosis, this study aims to provide insight about the possible links between fatty liver and the development of chronic kidney disease (CKD).SettingHospital.ParticipantsWe performed a population-based study on 9436 subjects aged 40 years or older.Primary and secondary outcome measuresFLI is calculated using an algorithm based on body mass index, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 38 publications
4
17
0
Order By: Relevance
“…Proteinuria also predicts patients at increased risk of adverse clinical outcomes regardless of the estimated glomerular filtration rate (eGFR) [ 6 ]. In addition, proteinuria has been regarded as a manifestation of endothelial dysfunction and systemic inflammation [ 7 ] and has recently been linked to the risk of chronic systemic inflammatory diseases [ 8 , 9 , 10 , 11 , 12 , 13 ]. However, there is no evidence on the impact of proteinuria on the incidence of IBD.…”
Section: Introductionmentioning
confidence: 99%
“…Proteinuria also predicts patients at increased risk of adverse clinical outcomes regardless of the estimated glomerular filtration rate (eGFR) [ 6 ]. In addition, proteinuria has been regarded as a manifestation of endothelial dysfunction and systemic inflammation [ 7 ] and has recently been linked to the risk of chronic systemic inflammatory diseases [ 8 , 9 , 10 , 11 , 12 , 13 ]. However, there is no evidence on the impact of proteinuria on the incidence of IBD.…”
Section: Introductionmentioning
confidence: 99%
“…Dyslipidaemia has always been regarded as the cornerstone of arteriosclerosis and the primary target of therapy according to international guidelines [11, 12]. In addition, it has been reported that dyslipidaemia associated with arteriosclerotic complications is the most common cause of death in chronic kidney disease (CKD) patients, and dyslipidaemia has also been shown to be an independent risk factor for the progression of CKD [13, 14]. Furthermore, a previous meta-analysis demonstrated that statins for treatment of dyslipidaemia may be beneficial for the reduction of albuminuria in CKD patients [15].…”
Section: Introductionmentioning
confidence: 99%
“…It has been estimated that 25% of the global population have non-alcoholic fatty liver disease (NAFLD), with highest prevalence in the Middle East and South America and lowest prevalence in Africa 1 2. Of greater concern is the association of fatty liver with extrahepatic diseases, such as type 2 diabetes, cardiovascular diseases (CVDs) and chronic kidney disease 3–5. It is therefore logical to speculate association of FLD with increased mortality risk consequent on the association of these diseases with increased mortality globally 6…”
Section: Introductionmentioning
confidence: 99%